2019
DOI: 10.1159/000501516
|View full text |Cite
|
Sign up to set email alerts
|

An Empirically Based Typology of Alcohol Users in a Community Sample Using Latent Class Analysis

Abstract: An empirically based typology of alcohol users in a Hungarian community sample using latent class analysis. European Addiction Research, in press. Short title: An empirically based typology of alcohol users in a community sample

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
(66 reference statements)
1
4
0
1
Order By: Relevance
“…While earlier typological models detected externalizing and anxio-depressive symptoms as hallmarks of separate subpopulations [15][16][17], our study identified that these could co-occur. This finding is also in line with the results of Horva ´th et al [30] who detected that a subgroup of alcohol users in a community sample is characterized by both increased externalizing and anxio-depressive symptoms. Based on our results, externalizing symptom characteristics not just have a group-forming role helping in disentangling the heterogeneity of the diagnostic category of AUD, but is suitable for detecting subgroups characterized with concomitant anxio-depressive features, thus a more severe subgroup of AUD.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While earlier typological models detected externalizing and anxio-depressive symptoms as hallmarks of separate subpopulations [15][16][17], our study identified that these could co-occur. This finding is also in line with the results of Horva ´th et al [30] who detected that a subgroup of alcohol users in a community sample is characterized by both increased externalizing and anxio-depressive symptoms. Based on our results, externalizing symptom characteristics not just have a group-forming role helping in disentangling the heterogeneity of the diagnostic category of AUD, but is suitable for detecting subgroups characterized with concomitant anxio-depressive features, thus a more severe subgroup of AUD.…”
Section: Discussionsupporting
confidence: 92%
“…That is, LPA can contribute to having more precise classification models than other, more arbitrary classification methods (e.g., splitting participants into categories based on median, and/or quartiles). The present analytical approach was in line with previous latent class analytic studies which examined the link between problematic alcohol use and psychopathological symptoms [30]. The estimated models contained three continuous and observed indicator variables: aggression, novelty seeking and impulsivity.…”
Section: Discussionmentioning
confidence: 88%
“…, 2015 ). Also, in alcohol users in general, higher levels of alcohol use are associated with higher levels of depressive symptoms ( Horváth et al. , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that other addictive disorders (e.g., alcohol dependence or other substance use disorders), out of the scope of the present study, might have worsened and/or displaced the behaviors studied during these stressful times ( Acuff et al, 2021 ; Xu et al, 2021 ). For example, alcohol use disorder was a prevalent health issue in Hungary before the pandemic ( Horváth et al, 2019 ; World Health Organization, 2019a ) and it might have increased during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%